Soil surface colonization by phototrophic indigenous organisms, in two contrasted soils treated by formulated maize herbicide mixtures - Joly, Pierre (Ecotoxicology (London, England), 2014)
Soil phototrophic microorganisms, contributors to soil health and food webs, share their particular metabolism with plants. Current agricultural practices employ mixtures of pesticides to ensure the crops yields and can potentially impair these non-target organisms. However despite this environmental reality, studies dealing the susceptibility of phototrophic microorganisms to pesticide mixtures are scarce. We designed a 3 months microcosm study to assess the ecotoxicity of realistic herbicide mixtures of formulated S-metolachlor (Dual Gold Safeneur(®)), mesotrione (Callisto(®)) and nicosulfuron (Milagro(®)) on phototrophic communities of two soils (Limagne vertisol and Versailles luvisol). The soils presented different colonizing communities, with diatoms and chlorophyceae dominating communities in Limagne soil and cyanobacteria and bryophyta communities in Versailles soil. The results highlighted the strong impairment of Dual Gold Safeneur(®) treated microcosms on the biomass and the composition of both soil phototrophic communities, with no resilience after a delay of 3 months. This study also excluded any significant mixture effect on these organisms for Callisto(®) and Milagro(®) herbicides. We strongly recommend carrying on extensive soil studies on S-metolachlor and its commercial formulations, in order to reconsider its use from an ecotoxicological point of view